Transforming Value of Vernacular Artifacts into Modern Utensils: A Case of Sukhothai Tableware - Charanya Phaholthep; Nopadon Sahachaisaeree (My University, 2012)
Abstract Vernacular objects usually reflected the value carried with the historical backdrop. Design features of utensils transformed from tradition-style needed to be functionally altered to meet the need of modern lifestyle yet still maintaining their traditional value. This research uses the Sukhothai artifacts as case study to analyze the particular design features of chinaware in this period and utilizes it as visual reference, embedding its identity into modern household utensils. Resultant from the study is utilized to set up a guideline for designing the modern household tableware that could reflect the vernacular handicrafts of the era. Finally, the findings also recommend a proper procedure by which vernacular artifacts is transformed into modern utensils.
Keywords: Value (mathematics); Crafts, Textile, and Design